2020
DOI: 10.1007/s13206-020-4106-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Biofluidic and Nanobiotechnology Approaches for Treating Sepsis in Extracorporeal Circuits

Abstract: Infectious diseases and their pandemics periodically attract public interests due to difficulty in treating the patients and the consequent high mortality. Sepsis caused by an imbalanced systemic inflammatory response to infection often leads to organ failure and death. The current therapeutic intervention mainly includes "the sepsis bundles," antibiotics (antibacterial, antiviral, and antifungal), intravenous fluids for resuscitation, and surgery, which have significantly improved the clinical outcomes in pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…While CytoSorb does not destroy or remove the virus, it has been used in more than 80,000 EU procedures as an approved treatment for cytokine storms. It has been distributed worldwide to 58 countries, helping doctors control severe inflammation, help reverse shocks, and improve breathing and other functions of the heart, which are some of the primary reasons patients suffer from CO­VID-19 infection [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…While CytoSorb does not destroy or remove the virus, it has been used in more than 80,000 EU procedures as an approved treatment for cytokine storms. It has been distributed worldwide to 58 countries, helping doctors control severe inflammation, help reverse shocks, and improve breathing and other functions of the heart, which are some of the primary reasons patients suffer from CO­VID-19 infection [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gold nanoparticles (AuNPs) may also exert their antiviral efficacy through hindering of gp120 fusion to CD4 that are surrounded by capping agents (encapsulated AuNPs) ( Table 1 ). Hybridized and charged AuNPs render virucidal mechanism after associating with nano-based formulation and mimicking peroxidase enzymatic reaction, where inhibited viral entry is facilitated by blocking of transcription within the host cell ( Isida, 2019 ; Kumar et al, 2020 , Kumar et al, 2020 , Kumar et al, 2020 ; Kang, 2020 ).…”
Section: Mode Of Action and Biomedical Applications Of Biocompatible mentioning
confidence: 99%
“…Most of the clinical trials were in experimental stages ( in vitro phase ) and some of them have received green signals as a post-exposure prophylaxis (i.e.advanced drug treatment options for SARS-CoV) ( Table 3 ). Many researchers ( Agostini et al, 2018 ; Kang, 2020 ) have found that corticosteroids with interferon alfacon-1 may have effective antiviral actions for such group of coronaviruses having RNA-dependent RNA polymerases. Gao et al (2020) and Gordon et al (2020) have reported that niclosamide, novavax and geovax might have the potential to inhibit virus-cell entry and virus replication.…”
Section: Metabolic Pathway Of Nanotherapeutics and Their Limitations mentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7] Severity of symptoms can be aggravated by an overwhelming cytokine storm associated with the presence of intact bacteria or of pathogen-associated molecular patterns (PAMPs) of fragmented bacteria in the blood stream. [8] Treatment includes source removal and infectioncontrol. [1] Infection-sources can be either an infection elsewhere in the body, skinpenetrating intravascular catheters, [9] ventilators, [10] or hemodialysis devices.…”
mentioning
confidence: 99%